Elastic analysis procedures: an incurable (but preventable) problem in the fertility effect literature. Comment on Gildersleeve, Haselton, and Fales (2014) - Harris, Christine R; Pashler, Harold; Mickes, Laura (Psychological bulletin, 2014)
Gildersleeve, Haselton, and Fales (2014) presented a meta-analysis of the effects of fertility on mate preferences in women. Research in this area has categorized fertility using a great variety of methods, chiefly based on self-reported cycle length and time since last menses. We argue that this literature is particularly prone to hidden experimenter degrees of freedom. Studies vary greatly in the duration and timing of windows used to define fertile versus nonfertile phases, criteria for excluding subjects, and the choice of what moderator variables to include, as well as other variables. These issues raise the concern that many or perhaps all results may have been created by exploitation of unacknowledged degrees of freedom ("p-hacking"). Gildersleeve et al. sought to dismiss such concerns, but we contend that their arguments rest upon statistical and logical errors. The possibility that positive results in this literature may have been created, or at least greatly amplified, by p-hacking receives additional support from the fact that recent attempts at exact replication of fertility results have mostly failed. Our concerns are also supported by findings of another recent review of the literature (Wood, Kressel, Joshi, & Louie, 2014). We conclude on a positive note, arguing that if fertility-effect researchers take advantage of the rapidly emerging opportunities for study preregistration, the validity of this literature can be rapidly clarified.